2013
DOI: 10.1155/2013/461829
|View full text |Cite
|
Sign up to set email alerts
|

Using Information and Communication Technology in Home Care for Communication between Patients, Family Members, and Healthcare Professionals: A Systematic Review

Abstract: Introduction. Information and communication technology (ICT) are becoming a natural part in healthcare both for delivering and giving accessibility to healthcare for people with chronic illness living at home. Aim. The aim was to review existing studies describing the use of ICT in home care for communication between patients, family members, and healthcare professionals. Methods. A review of studies was conducted that identified 1,276 studies. A selection process and quality appraisal were conducted, which fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
166
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(180 citation statements)
references
References 114 publications
6
166
0
8
Order By: Relevance
“…The ICT in home care is mostly used as a tool for communication between healthcare professionals and patients or family members. Healthcare professionals can base on this result, advantageously use ICT applications in home care as a tool to support people living with chronic illnesses gaining control of their ailment that promotes self-care [13]. In addition, the e-health systems can have a beneficial impact on the process of clinical and home care in low-and middleincome countries [14].…”
Section: Obligation Of Home Care Education For Tracheostomymentioning
confidence: 99%
“…The ICT in home care is mostly used as a tool for communication between healthcare professionals and patients or family members. Healthcare professionals can base on this result, advantageously use ICT applications in home care as a tool to support people living with chronic illnesses gaining control of their ailment that promotes self-care [13]. In addition, the e-health systems can have a beneficial impact on the process of clinical and home care in low-and middleincome countries [14].…”
Section: Obligation Of Home Care Education For Tracheostomymentioning
confidence: 99%
“…Currently, healthcare providers have a seemingly infinite combination of graphic, textual, coded, statistically analyzed, collated, filtered, non-filtered and malleable data [23]. As a result, healthcare organizations endeavour to construct comprehensive summary views of patient's medical records.…”
Section: Healthcare and Ictmentioning
confidence: 99%
“…In a study undertaken by [23], an exhaustive survey was conducted for the use of ICT in healthcare. Here, definitions of tele-health and tele-medicine along with e-health and an appraisal of mechanisms to weigh the ICT interventions in health were discussed.…”
Section: Healthcare and Ictmentioning
confidence: 99%
“…Several reviews have already proven and indicated the rising importance of the use of information technology (IT) in healthcare [4,5]. The past years, there has been an uptake in the use of personal, smart devices [6,7].…”
Section: Introductionmentioning
confidence: 99%